Brick model for nonlinear deformation and microcracking in thermal barrier coating - Eito YONEMICHI (The Japan Society of Mechanical Engineers, 2020)
Thermal barrier coatings (TBCs) applied to turbine blades indicate nonlinear deformation and complex fracture behavior due to the microstructure which is formed by deposition of molten particles. In this study, in order to accurately simulate these behaviors observed in TBC, finite element analysis based on the brick model combined with cohesive model and the inelastic constitutive equation was established. First, bending tests of freestanding YSZ sample specimens extracted from TBC-coated sample deposited under different particle velocity conditions were performed to identify its deformation and fracture behaviors prior to FE analysis. As a result, the bending test revealed that the maximum load, the maximum deflection, and the crack propagation path varied significantly depending on the particle velocity. Subsequently, the FE procedure combined with the brick and inelastic constitutive models was developed, and it was confirmed that the FE analysis based on the brick model can accurately simulate nonlinear deformation and complex crack propagation path observed in a micro-scale.